Scientific production on swimming in Portuguese language: a bibliometric analysis Produção cientifica sobre natação em língua portuguesa: uma análise bibliométrica Producción científica sobre natación en lengua portuguesa: un análisis bibliométrico - de Souza K.K.* (2022)
© Este é um artigo Open Access sob uma licença CC BY-NC-ND (http://creativecommons.org/licenses/by-nc-nd/4.0/)This study analyzed the scientific production on swimming in Portuguese through bibliometrics. Scientific Electronic Library Online, Biblioteca Virtual em Saúde and Scopus databases were searched from their inception until September 2022. Two hundred and thirty-two studies were included. Scientific production increased considerably in the last two decades, being mainly concentrated in the Southeast and South regions, in journals classified as A2 to B2 in the Qualis-CAPES 2013-2016. Biomechanics and physiology were the most studied areas. Most studies are of a quantitative, observational, and cross-sectional nature, and included adolescent and athlete populations. The quantity and variety of studies demonstrates the interest in investigating aspects related to swimming